TINJAUAN KRIMINOLOGI TERHADAP ANAK KANDUNG SEBAGAI PELAKU TINDAK PIDANA PERCOBAAN PEMBUNUHAN BERENCANA TERHADAP AYAH - Jannah, Yunita Roudhotul; Kartika, Adhitya Widya (Gapenas Publisher, 2023)
In this study, the author uses the empirical juridical method, research that races against the actual situation that exists in society with the aim of finding the facts and data needed. This study aims to determine and understand the criminological review of biological children as perpetrators of attempted murder of fathers. Sources of research data obtained by interviews and research data is also obtained from legislation and literature or literature. There were 2 cases of biological children as perpetrators of attempted murder of fathers in Lamongan from 2018 to 2021, with 2 perpetrators. The judge's basis for consideration in the decision related to the case of the biological child as the perpetrator of the attempted murder of the father is based on facts, circumstances, evidence, and viewed from the criminology side, so that it can be the basis for determining the defendant's guilt. The author conducts a criminological analysis with an approach to modern criminological theory and to find out what factors cause someone to commit a crime, and in this theory also argues that someone who commits a crime has weak social ties, in the response efforts provided by the Lamongan Resort Police and also obstacles. The problems faced are related to the case of biological children as perpetrators of attempted murder of fathers by providing socialization on prevention of criminal behavior to the community in urban, rural areas and schools in Lamongan, and also carrying out routine sharp weapons operations which are held every 1 month